Relationship of smoking cessation duration and cognitive function among middle-aged and older adults in China: a national cross-sectional study - Zuo, Wenhang; Peng, Jin; Wu, Jinhui (Frontiers in Public Health, 2025)
BackgroundPopulation aging and smoking are both major challenges worldwide, particularly in developing countries. We preliminarily explored the relationship of smoking cessation duration and cognitive function among middle-aged and older Chinese.MethodsThe data comes from China Health and Retirement Longitudinal Study (CHARLS) wave 4. Smoking information was collected by standardized questionnaire. Global and memory-specific cognitive functions were assessed. We used restricted cubic spline to explore curvilinear relationship. After discretizing the duration of ex-smokers (quitting ≤2 years, 3–8 years, 9–19 years, and ≥20 years), multiple linear regression models were established with current smokers as reference.ResultsA total of 5,561 respondents (67.7 ± 6.2 years; 54.1% men) were included. Respondents who quit smoking for longer showed better global cognitive function. This trend leveled off among respondents who had quit smoking for ≥20 years. There were significant differences in global cognitive function among those who quit smoking for ≥9 years (9–19 years, β = 0.75, 95%CI 0.32–1.18; ≥20 years, β = 0.94, 95%CI 0.42–1.46). The differences mainly came from men. In immediate memory, all ex-smokers performed better. In delayed memory, only those quit for ≥9 years had significant differences.ConclusionCompared with current smokers, both never smokers and ex-smokers showed better cognitive function. Respondents who quit smoking for longer had better cognitive performance, especially those who had quit for at least 9 years.